2013
DOI: 10.1371/journal.pone.0059874
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Transmission EPR Spectroscopy

Abstract: EPR spectroscopy employs a resonator operating at a single microwave frequency and phase-sensitive detection using modulation of the magnetic field. The X-band spectrometer is the general standard with a frequency in the 9–10 GHz range. Most (bio)molecular EPR spectra are determined by a combination of the frequency-dependent electronic Zeeman interaction and a number of frequency-independent interactions, notably, electron spin – nuclear spin interactions and electron spin – electron spin interactions, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Other studies have reported the use of analog or digital, scalar or vector network analyzers as source/detector of EPR 3235 including my own work. 3 None of the cited papers provide examples of multifrequency data of high quality from randomly oriented, dilute transition ion complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported the use of analog or digital, scalar or vector network analyzers as source/detector of EPR 3235 including my own work. 3 None of the cited papers provide examples of multifrequency data of high quality from randomly oriented, dilute transition ion complexes.…”
Section: Discussionmentioning
confidence: 99%
“…This result deviates from past studies on nonresonant ESR detection reports where sensitivity was a major hindrance. 12,13 A further examination of Figure 6a illustrates the transmission line probe approach has sufficient sensitivity to probe much lower microwave excitation powers than usually accessible in commercial systems. This is particularly advantageous when measuring a spin system with long relaxation times.…”
Section: ■ Experimental Setupmentioning
confidence: 98%
“…This design facilitates easy exchange of samples and eliminates contamination of the transmission line probe. A simple schematic of the design is shown in Figure 3 disadvantage, 12,13 the nonresonant nature (Q ∼ 1) suggests that the measurement will suffer from low sensitivity due to the lack of amplification in ESR excitation and detection. The excitation shortfall can be remedied by increasing the amplitude of the input signal (as discussed above).…”
Section: ■ Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Electron paramagnetic resonance (EPR) is a technique that probes transitions between electron-spin quantum states (m S ), rather than nuclear-spin quantum states (m I ) observed by NMR. 75 Electron paramagnetic resonance is used to study the spin-state in paramagnetic complexes. 76 The technique is used to characterize complexes is often the modulation of transient zero-field splitting (ZFS).…”
Section: Nuclear Magnetic Resonance and Electron Paramagnetic Resonancementioning
confidence: 99%